INVESTIGATING GRAMMATICAL ERRORS IN RECOUNT TEXT WRITTEN OF EFL LEARNERS - Sadapotto, Andi; M, Usman (Uniqbu Journal of Social Sciences, 2022)
This research aimed to find out the most frequent errors that the students made in writing recount text. This research used descriptive method with quantitative data analysis technique to answer proposed question. The scope of this researh is limited to grammatical analysis and the mechanics of writing components to the forthy recount texts written by the third year studentts of STKIP Muhammadiyah Rappang. The errors were classified into six categories : errors in using verb form; thr use of article; the use of preposition; noun pluralization; the use of pronoun; the use of conjunction. The research findings indicated that the most frequent errors made by the students were in using verb form, punctuation, preposition, noun, article, and pronoun. It can be inferred that the students have not mastery the grammar well. They face a lot of problems English language in general and in particular in writing the English language.